Analisis Tingkat Kenyamanan Ruang Terbuka Hijau Publik pada Taman Alun-Alun Merdeka Kota Malang - Febiola, Merian Friska; Soelistyari, Hesti Triana; Alfian, Rizki (http://arl-faperta.ipb.ac.id/, 2024)
Merdeka Square Park in Malang City is one of the parks which is a favorite place for the people of Malang to do recreation. Apart from being a favorite place, the location of this park is also very strategic, which is right in the middle of the city or directly adjacent to the main road where many vehicles pass. Based on the location of this park, it is necessary to conduct research related to the level of comfort in the park based on visitor perceptions and the level of thermal comfort. This research was conducted to determine the level of comfort that exists in Merdeka Square Park, Malang City. The research method used is THI (temperature humidity index) to analyze the level of thermal comfort and the Likert scale to analyze the comfort level of the park based on visitor perceptions of nine indicators or influencing factors, namely beauty, cleanliness, safety, circulation, shape, aroma/smell- smell, noise, lighting, and climate. Based on the results of the study, it was found that this park has an average THI value of 25.8 0 C with a fairly comfortable category. Then, for the level of comfort based on visitor perceptions, it was found that the indicators of beauty, safety, circulation, shape and climate fall into the very comfortable category. Meanwhile, for indicators of cleanliness, aroma/odors, noise, and lighting fall into the quite comfortable category.